2017
DOI: 10.1007/s40264-017-0535-0
|View full text |Cite
|
Sign up to set email alerts
|

Communication on Safety of Medicines in Europe: Current Practices and General Practitioners’ Awareness and Preferences

Abstract: IntroductionNational competent authorities (NCAs) for medicines coordinate communication relating to the safety of medicines in Europe. The effectiveness of current communication practices has been questioned, particularly with regard to reaching general practitioners (GPs).ObjectiveThe aim of this study was to assess current European NCA safety communication practices and to investigate European GPs’ awareness of and preferences for safety communications on medicines.MethodsWeb-based surveys were distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 11 publications
1
50
0
Order By: Relevance
“…To improve the understanding of the PIL and to promote their use, several measures, such as the inclusion of short, structured and visual/text explanations, have been proposed . Competent authorities for the regulation of medicines in several European countries have recently reviewed their practices regarding communication about the safety of medicines …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the understanding of the PIL and to promote their use, several measures, such as the inclusion of short, structured and visual/text explanations, have been proposed . Competent authorities for the regulation of medicines in several European countries have recently reviewed their practices regarding communication about the safety of medicines …”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Competent authorities for the regulation of medicines in several European countries have recently reviewed their practices regarding communication about the safety of medicines. [30] Some previous studies [27,31,32] have indicated that information on drug safety is the most-read part of the PIL. However, in our study, only the population that occasionally read the PIL reported this preference.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that there is variation between countries in Europe in GP preferences for the format of safety communications. [28] Despite this, it appears that DHPCs represent the most common source of awareness of medicines' safety issues among European GPs, pharmacists and cardiologists. [29] Previous research has indicated that such communications have greater impact on non-specialist drugs and for safety issues with a risk of death and/or disability, [8] however to date, the relationship between characteristics of DHPCs and variation in outcomes has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Such discussions are largely conducted in confidence and should be more transparent. Additionally, the issuance of safety communications by sponsors might affect the trust with which they are received 3536. Although European doctors have indicated that they prefer to receive safety advisories from regulators rather than industry,3536 a key form of safety advisory in the EU are letters from sponsors with text agreed by regulators.…”
Section: Reasons For Differences In Communication and Their Implicationsmentioning
confidence: 99%